2022
DOI: 10.3991/ijet.v17i15.31843
|View full text |Cite
|
Sign up to set email alerts
|

Improvisation of Music Therapy with Repertoire of Marineras Trujillanas in Online Higher Education Learning

Abstract: University students face and faced cases of anxiety, stress, shyness in front of the public which caused effects on learning and if it was online learning were stronger those negative effects, so the improvisation music therapy with workshops had to intervene as a fundamental tool in online learning, the objective of this research was to analyze the results of the development of an improvisation music therapy program, with Peruvian marinera repertoire in general studies students of the music workshop of the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…There are researches with positive effects of music in students of all educational levels with the use of musical digital competences which should be suggested or increased in musical workshops at all educational levels to maintain active learning and psychological excitement of students (Alburqueque et al, 2022), this kind of applications surprised the university education in workshops and online presentations because the objective of digital competences is to moderate the relationship of education with hybrid education to maintain active digital competences of students in all branches of science and interacting with the same society. There is also evidence of digital competences in the application of languages whose results were successful in terms of coherence and cohesion, content, vocabulary adequacy and richness as well as grammatical correctness (Mykytiuk et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are researches with positive effects of music in students of all educational levels with the use of musical digital competences which should be suggested or increased in musical workshops at all educational levels to maintain active learning and psychological excitement of students (Alburqueque et al, 2022), this kind of applications surprised the university education in workshops and online presentations because the objective of digital competences is to moderate the relationship of education with hybrid education to maintain active digital competences of students in all branches of science and interacting with the same society. There is also evidence of digital competences in the application of languages whose results were successful in terms of coherence and cohesion, content, vocabulary adequacy and richness as well as grammatical correctness (Mykytiuk et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that digital competencies are being empowered not only in higher education, but also in T Perspectives on Digital Competencies in University: What's Ahead for Education? education for children where digital competencies in music are being used because teachers are practicing educational praxis with the ICT approach because in higher education digital competencies in music are already being improvised in the classroom either in person or virtually to combat stress and anxiety in university students (Alburqueque et al, 2022). The causes of digital changes and transformations that occurred because of not having physical exchanges with society (pandemic era) has affected the performance and academic productivity of students although we know that digital competencies is the set of attitudes, skills and abilities that were cultivated to achieve use or manage technologies in the right way for the good of cognitive development in the education sector (Rodríguez-Garcia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…En Perú, se ha observado una tendencia similar. Mayorca-Martínez et al ( 2023) y Puma-Chavez et al ( 2022) han destacado la relación entre el uso de redes sociales y la autoestima, así como el papel de la terapia de música de improvisación en la mejora del bienestar estudiantil Alburqueque et al (2022). Sin embargo, persiste una necesidad de entender en profundamente cómo el tiempo dedicado al consumo de contenidos audiovisuales y la elección de diferentes tipos de medios afectan específicamente la autoestima de los estudiantes universitarios.…”
Section: Introductionunclassified